Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The above expression popped up in a problem I was solving. Using the relation $$i=\exp(i\pi/2)$$ I got $$\frac{1}{\sqrt{\pm i}}=\exp(\mp i\pi/4),$$ however, the reference I have gives the result as $$\frac{1}{\sqrt{\pm i}}=\exp(\pm i\pi/4).$$ Please could someone point out my mistake or show how to properly evaluate the expression.

share|cite|improve this question
$\sqrt {\pm i}$ has four values, so you're both wrong. – Chris Eagle Jan 4 '13 at 13:47
@ChrisEagle: Okay. Can you please show how to evaluate? – Jonjo Jan 4 '13 at 13:53
up vote 5 down vote accepted

$i$ has modulus $1$ and argument $\pi/2$, so one of the square roots of $i$ has modulus $1$ and argument $\pi/4$, while the other is the negative of this one, so it has modulus $1$ and argument $5\pi/4$. Then the two values of $1/\sqrt i$ have modulus $1$ and arguments $-\pi/4$ and $-5\pi/4$.

Similarly approach for $-i$, which has modulus $1$ and argument $3\pi/2$.

share|cite|improve this answer
Mine is sooooo elementary than yours, Gerry and Clive. :( – Babak S. Jan 4 '13 at 13:59
@Babak, whatever floats your boat. I'm not sure what's non-elementary about modulus and argument. – Gerry Myerson Jan 4 '13 at 14:08

I am trying to show you how to find $z=\sqrt{x+yi}$. Let $z=\sqrt{x+yi}=a+bi$ so $$(\sqrt{x+yi})^2=(a+bi)^2$$ If you do the latter identity, you will find $$(1): a^2-b^2=x;(2):2ab=y$$ and $$(3):(a^2+b^2)^2=\sqrt{x^2+y^2}$$ $(1)+(3)$ gives you $$2a^2=\sqrt{x^2+y^2}+x$$ and $(1)-(3)$ gives you $$2b^2=\sqrt{x^2+y^2}-x$$ Now, the only thing you should kow is what is $\frac{1}{a+ib}$

share|cite|improve this answer

$$\pm i=e^{\pm\pi/2}\Longrightarrow \sqrt{\pm i}=\pm e^{\pm\,\pi/4}\Longrightarrow\frac{1}{\sqrt{\pm i}}=\left(\sqrt{\pm i}\right)^{-1}=$$

$$\pm e^{\mp \pi/4}=\pm\left(\cos\frac{\pi}{4}\mp i\sin\frac{\pi}{4}\right)=\pm\frac{1}{\sqrt 2}\left(1\mp i\right)$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.